Mathematical Literacy Research in Mathematics Learning: Bibliometric Review - Maharani, Swasti; Hendrisa Rizqie Romandoni; Tiara Citra Maharani Firdaus; Muhammad Noor Kholid; Widia Yunita (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to identify and analyze publications related to mathematical literacy in the mathematics learning process. The method used is descriptive bibliometric analysis with the use of dimension databases that include research data for the last 10 years. The results of the analysis show that the peak of publications occurred in 2022 with 105 relevant publications. "Journal of Physics" and "AIP Conference Proceedings" are the two most frequently cited sources in the study. Additionally, Indonesia, China, and the United States collectively exerted the most significant influence in this study. Additionally, Indonesia, China, and the United States collectively exerted the most significant influence in this study. The results of the analysis also revealed that the focus of research related to mathematical literacy in mathematics learning covers several main topics, namely, 1) mathematical literacy, child, 2) textbook, question, school, 3) learning, practice, classroom 4) bilingual education. These findings provide valuable insights into research developments and trends in the domain of mathematical literacy in the context of mathematics learning.